The primary study of peat soil in wood plastic composite - Alias, Mohd Fairuz; Mustapa, Mohammad Sukri; Yusof, Yusri (Science and Engineering Research Support Society, 2020)
The major factor driving the growth of the global wood plastic composite (WPC) market is the increasing use of wood plastic composites by the construction and construction sectors for various applications. However, the current WPC is worth examining as this composite can be analyzed by increasing its strength. Therefore, this study was conducted to study the effect of peat soil (PS) on the mechanical properties of wood plastic composite systems reinforced with kenaf fibers. This study uses 4 different composite proportions of i) 10% kenaf fiber and 90% polypropylene ii) 20% kenaf fiber and 80% polypropylene iii) 30% kenaf fiber and 70% polypropylene and iv) 40% kenaf and 60% polypropylene fiber with peat soil added 3%, 6% and 9%. The particle size for peat is 60μm. The method used to produce this wooden plastic composite is by mixing method and injection molding.The test performed on the sample is tensile test and flexural test. The results of tensile test are determined and show that 6% PS is reinforced with 10% KF and 90% PP has the highest tensile strength of 25.23 MPa. While the best results of flexural test were obtained with 3% PS reinforced with 10% KF and 90% PP had a maximum bending strength of 32.40 MPa.